Improvement of concrete durability proceedings of the seminar How to make today's concrete durable for tomorrow organized by the Association of Municipal Engineers of the Institution of Civil Engineers and held in London on 8 May, 1985. (Thomas Telford, 1986)
A book which outlines the requirements for durable concrete and the use of pulverized fuel ash to produce durable concrete.